2015
DOI: 10.3892/ijo.2015.2877
|View full text |Cite
|
Sign up to set email alerts
|

YAP/TAZ for cancer therapy: Opportunities and challenges (Review)

Abstract: YAP (Yes-associated protein) and its paralog TAZ (transcriptional co-activator with PDZ-binding motif) are the main downstream effectors of the Hippo signaling pathway. This pathway is an evolutionally conserved signal cascade, which plays pivotal roles in organ size control and tumorigenesis from Drosophila to mammals. Functionally, when the Hippo pathway is activated, YAP and TAZ will be sequestered in the cytoplasm and degraded. Conversely, when the Hippo pathway is deactivated, YAP and TAZ will translocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 88 publications
(89 reference statements)
2
99
0
Order By: Relevance
“…For example, YAP specifically binds to ErbB4 and p73, whereas TAZ specifically binds to PPARc, Pax3, TBX5, and TTF-1. 57 In line with these results, we observed that FN1, COL1A1, and COL4A1 were specifically suppressed by silencing of YAP. Thus, it is likely that YAP, but not TAZ, can interact with a unique subset of transcription factors to induce the expression of FN1, COL1A1, and COL4A1 on TGF-b2 stimulation.…”
Section: Discussionsupporting
confidence: 78%
“…For example, YAP specifically binds to ErbB4 and p73, whereas TAZ specifically binds to PPARc, Pax3, TBX5, and TTF-1. 57 In line with these results, we observed that FN1, COL1A1, and COL4A1 were specifically suppressed by silencing of YAP. Thus, it is likely that YAP, but not TAZ, can interact with a unique subset of transcription factors to induce the expression of FN1, COL1A1, and COL4A1 on TGF-b2 stimulation.…”
Section: Discussionsupporting
confidence: 78%
“…A wealth of evidence has emerged that deactivation of the Hippo pathway and up-regulation of TAZ were observed in a wide spectrum of human cancers, suggesting that inactivation of TAZ could be a promising strategy for the treatment of cancers [39]. For example, microRNA-129-5p inhibited ovarian cancer cell proliferation and survival through suppression of TAZ [40].…”
Section: Discussionmentioning
confidence: 99%
“…YAP, first reported in 1994 as a binding partner of the SH3 domain of the Yes proto-oncogene product [12], is a key downstream effector of the Hippo signaling pathway. When the Hippo pathway is deactivated, YAP can translocate to the nucleus to activate gene expression by associating with a number of DNA-binding transcription factors, modulating diverse cellular functions, including proliferation, apoptosis, migration and differentiation [13, 14]. YAP is generally overexpressed in tumor tissues [1517], and has been reported to modulate the epithelial-mesenchymal transition (EMT) and various pathways that are important for resistance to chemotherapy [18, 19].…”
Section: Introductionmentioning
confidence: 99%